Merencanakan Keamanan Jaringan Komputer - Joni Suhartono (ComTech: Computer, Mathematics and Engineering Applications, 2011)
Communication via wireless devices provides many benefits to companies and users, such as portability and flexibility, productivity improvement, and low installation fee. Wireless technology covers a variety of abilities on use and needs. A WLAN device as an example allows users to get mobile from a place to another without wires attached and connection loss. Wirelesss means more flexible, more efficient, and cost reduced. Adhoc network such as Bluetooth allows for data synchronization with network system and sharing application among devices. Bluetooth functions to diminish wires for printers and other supporting devices. Portable devices such as PDA and cell phone allow remote users to synchronize personal databases and provide accesses to email, browsing, and internet access. Thus, security risks are very influential on wireless network. Some of the risks are almost the same as the wired network, few are derived from other cable networks and some others are new.